Design of Solar Electric Bicycle Based on Pulse Width Modulation on Throttle as DC Motor Speed Regulator - Fadly, Singgi; Irianto, Chairul Gagarin; Alam, Syah (International Journal Labs, 2024)
Electric bicycles are designed to use renewable energy to support the government's efforts to reduce carbon emission consumption. Problems in every region or city regarding fueled vehicles certainly increase air pollution. Generally, electric bicycles are designed to be a solution and are used in daily life to carry out daily activities by requiring a bicycle gas throttle control that can assist the driver or person in controlling the speed of the electric bicycle. In this study, designing a solar electric bicycle as environmentally friendly energy based on PWM signals to determine the duty cycle value or duty cycle with an optimized PWM value can affect the speed system (km / h) in Revolutions Per Minute (RPM) to determine the performance of the DC motor. The electric bicycle uses 30Wp solar power, two 12V 7.5 Ah batteries assembled in series, and a 24V 250W DC brushless motor. Based on the design results with a total weight of 37kg electric bicycle plus the weight of 55kg, 65kg, 75kg, and 85kg driver variations, the total controller power value is 163.44 watts. The results of duty cycle testing (duty cycle) were 25%, 50%, 75%, and 98%, with 249.9 as the maximum value of PWM and 9.8 Vout generated against the maximum speed of the electric bicycle of 2648 RPM or the equivalent of an electric bicycle speed of 18-28 km/hour. In this case, the electric bicycle is in a condition suitable for use to carry out daily activities by utilizing clean, cheap and appropriate energy